The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.24815/ijdm.v5i2.27087
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Review on Disaster Management Models and Their Contributions

Abstract: This qualitative study aimed to undertake a critical examination of the models by thematic analysis to determine their contribution to disaster management. A review and analysis of the literature were used. The models were studied to explore their contribution to disaster management and to identify any significant constraints or challenges which could limit the ability of the models to carry out appropriate disaster risk reduction actions. The study found that such models are indispensable because they simplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Another study by Poonia et al (2022) revealed that 82% of drought cases in Central India were attributed to dry soil moisture. In order to anticipate the threat of drought in the area study, a long-term disaster management plan is essential as a reference for policymaking when a disaster occurs (Alrehaili et al, 2022;Ruswandi & Maarif, s2023). However, the study findings indicate that such a document must be available at the East Lombok Regency BPBD Office.…”
Section: Drought Disaster Mitigation Policymentioning
confidence: 99%
“…Another study by Poonia et al (2022) revealed that 82% of drought cases in Central India were attributed to dry soil moisture. In order to anticipate the threat of drought in the area study, a long-term disaster management plan is essential as a reference for policymaking when a disaster occurs (Alrehaili et al, 2022;Ruswandi & Maarif, s2023). However, the study findings indicate that such a document must be available at the East Lombok Regency BPBD Office.…”
Section: Drought Disaster Mitigation Policymentioning
confidence: 99%
“…Jalur yang menuju rumah sakit harus efektif baik dari segi keamanan dan perlindungan. Akses tersebut mencakup akses kendaraan dan pejalan kaki 14 .…”
Section: Status Kesiapsiagaan Rsu Aliyah 2 Kendariunclassified
“…Manajemen bencana bertujuan untuk mengurangi atau menghindari potensi kerugian akibat bencana, menjamin bantuan yang cepat dan tepat kepada korban bencana, dan mencapai pemulihan yang cepat dan efektif [17]. Siklus manajemen bencana tersebut terdiri dari mitigasi dan kesiapsiagaan, tanggap darurat dan pemulihan [2] [16]. Upaya mitigasi dan kesiapsiagaan dilaksanakan sebelum bencana terjadi, sedangkan upaya tanggap darurat terjadi saat bencana terjadi dan upaya pemulihan terjadi setelah bencana.…”
Section: Tinjauan Literaturunclassified